Psychological Dynamics of Online Gambling in Digital Era: Systematic Literature Review - Nisrina Widi Andini; Muhammad Salis Yuniardi; Istiqomah Istiqomah (Greenation Publisher & Yayasan Global Research National, 2026)
Online gambling is the act of betting money or goods online. Its impacts range from physical and mental health issues to extreme cases such as suicide. This systematic review of 11 international and national journal articles aims to identify the factors that influence online gambling behavior. The results of this systematic review indicate that factors influencing gambling behavior can originate from both internal and external sources. The most influential factors are self-control, ease of access, environment, and mental health status. Other factors include personality traits, sensation seeking and curiosity, the impact of the pandemic, as well as emotional regulation and cognitive distortions. These findings provide valuable information, serving as part of an effort to raise awareness and as a foundation for future research.